Fra Hamann til Fasc. 209.10. Om Grundtvigs forhold til Johann Georg Hamann og dennes samtidige - Christensen, Bent (Grundtvig-studier, 2012)
Fra Hamann til Fasc. 209.10. Om Grundtvigs forhold til Johann Georg Hamann og dennes samtidige[From Hamann to Fascicle 209.10. On Grundtvig's relation to Johann Georg Hamann and his contemporaries]By Bent Christensen The German critic and Enlightenment philosopher Johann Georg Hamann (1730-88) can be seen as a German forerunner of Grundtvig who according to a few places in his Verdenskrøniken (World Chronicle), 1817, has known about his writings and perhaps felt a spiritual kinship to him. By all accounts, the only other mention of him at all by Grundtvig occurs in a brief and somewhat enigmatic manuscript entitled “ Synchronismer” (synchronisms) (The Grundtvig Archive, Fascicle 209 nr 10). It lists names of 24 German authors supplied with dates marking periods in their careers between the years 1741 and 1781 and has been regarded as a preliminary study for the World Chronicle 1817. But it can also be seen as a view of these authors from a specific “synchronistic” angle, resulting in a particular profile of these 40 years. The list also reflects Grundtvig’s detailed knowledge of German literary history.After a presentation of Hamann, Grundtvig’s evaluation of him in the World Chronicle of 1817 is quoted and commented upon, followed by a an examination of the manuscript list author by author, inclusive of references to treatments in the World Chronicle.The list begins with “ Rabener 1741-57” and finishes with “Bürger 1769- 78”; the latest year brought up, however, is “1781” (under the names of Kant and Hamann). In his World Chronicle, Grundtvig states that the period he wants to depict, covers the reign of the Prussian king Frederick the Great (1740-86). The list corresponds almost exactly to this ambition. Hamann’s first year, 1759, is the year in which Sokratische Denkwürdigkeiten appeared, his first work addressing a general public. Hamann’s last year, 1781, indicates that he at that time started to write a critical review of Kant’s Kritik der reinen Vernunft, having read the proofs of it, as a personal friend of the philosopher, before its publication that same year. At first, however, Hamann did not print his text but only communicated it to Herder in a personal letter. The Metakritik über den Purismum der Vernunft was finished in 1784 but not published until 1800. When Kant in his work asks for a foundation of cognition prior to and independent of experience, Hamann accuses him of aiming at constituting a new kind of metaphysics. Two later works published by Hamann (1784 and 1786) are of a retrospective and summary nature.Concerning the other authors listed, the “first year” in most cases presents the very first step in their literary careers, and the “last year” marks the ending of their initial period. This applies, for example, to Rabener’s “last year”, 1757, when his satires had started already to appear in book form. In Lessing’s case, 1761 is the year in which he accepted a position as secretary for the governor of Breslau. Wieland was appointed town clerk in Biberach in 1760, but in the World Chronicle Grundtvig emphasizes the importance of his Shakespeare translations which did not begin to appear until 1762, though it is likely that Wieland had been encouraged to take up this project as early as 1759. Herder’s “last year” is 1767, the date of publication featured on the title page of Fragmente über die neuere deutsche Literatur—a date often considered to be the prime year of the “ Sturm und Drang” (“ Storm and Stress”) movement. Goethe’s “last year” is 1774 due to the publication of his best-seller novel Die Leiden des jungen Werthers.In several cases the often paired dates of Grundtvig’s list differ from those found in ordinary histories of literature as well as in the World Chronicle of 1817. A closer study of them—and a study of Grundtvig as compared to Hamann—might cause important contributions to Grundtvig research and to the study of German intellectual and literary history.